2019
DOI: 10.1039/c9cp03422f
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Dzyaloshinskii–Moriya spectral broadenings in promoting spin decoherence: a comparative pulsed-EPR study of two structurally related iron(iii) and chromium(iii) spin-triangle molecular qubits

Abstract: Two related iron(iii) and chromium(iii) spin-triangle molecular qubits show coherent driving of their spins, and decoherence that is not significantly affected by Dzyaloshikskii–Moriya spectral broadenings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“… a The values of the parameters refer to the formalism of Hamiltonian (). Effective g values in frozen pyridine solutions are taken from ref . b (2 J + J′ )/3. c | J – J′ |. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… a The values of the parameters refer to the formalism of Hamiltonian (). Effective g values in frozen pyridine solutions are taken from ref . b (2 J + J′ )/3. c | J – J′ |. …”
Section: Discussionmentioning
confidence: 99%
“…Here we investigate the factors that determine the strength of the ME coupling in two molecular spin qubits we have previously studied, the magnetoelectric Fe 3 , and its Cr III analogue [Cr 3 O­(PhCOO) 6 (py) 3 ]­ClO 4 ·0.5py ( Cr 3 ), whose close structural and chemical features make them an ideal couple for this purpose. We discover coherent electric control of the magnetization and unprecedented features regarding the anisotropy and dynamic nature of the ME coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The insets show the Fourier-transform spectraoft he data.A dapted from ref. [192]with permissionf rom the PCCP Owner Societies.…”
Section: Spin Chirality Qubits and Magnetoelectric Couplingsmentioning
confidence: 99%
“…[132] In view of the importance of DMI in the development of spin chirality and magnetoelectric couplings in spin triangles (see section 7.2), ak ey question is whether DMI-induced spectral broadenings accelerate decoherence owing to incomplete spectrale xcitationsa nd concomitants pectral diffusion. [191] Comparative pulsed EPR study of the closely related Fe 3 and Cr 3 [192] revealed that the pronouncedD MI-induced spectral broadening of Fe 3 does not have as ignificant impact on coherence times (Figure 9). Actually,i tw as shown that Fe 3 had consistently largerc oherence times than Cr 3 and practically the same coherence time as Fe 3 -salox,w hich had exhibited nil DMI.…”
Section: Spin Trianglesasq Ubitsmentioning
confidence: 99%
“…Therefore, the determination of the widths and shapes (Gaussian, Lorentzian or Voigtian) of eventual zfs distributions, which may prove significant in their consideration as spintronic materials. Indeed, one of us very recently commented on the effects of spectral broadenings on coherence times of spin qubits [35]. Due to the relevance of zero-field splitting (ZFS) in the appearance of the satellite features, and due to the minor influence of ligand-field effects on the g-tensor components and in inducing gstrains (see below), only a D-strain model was considered in order to account for parameter distributions, assuming that the g-tensor components are monodisperse.…”
Section: Epr and Electronic Spectramentioning
confidence: 99%